Role of serum albumin and body mass index in the outcome of major elective abdominal surgery - Lohe, Yepeto; V., Sreejith; Sharma, Raghvendra; Lombi, Nyage; M., Harish; G., Ankon; Sorhie, Viketoulie Samuel; Chader, Lakhi; Devi, Ranita (International Surgery Journal, 2019)
Background: The prevalence of protein-energy malnutrition in surgical patients is high, ranging from 10% to 54%. The correct assessment of the nutritional studies of such patients is crucial since malnutrition is a risk factor for morbidity and mortality. There is a substantial evidence to show that patients who have signs of malnutrition have a higher risk of complications and an increased risk of death in comparison with patients who have adequate nutritional reserves. Methods: 150 patients were selected for the study. All the collected data was entered in Microsoft Excel sheet. It was then transferred to SPSS ver. 21 software for statistical analysis. Quantitative data was compared by using student’s t-test and chi-square test, qualitative data compared using frequency, standard deviation and percentage. P<0.05 considered as significant. Results: The mean serum albumin was found to be 3.7 gm%±0.3. There was increase rate of complication and duration of hospital stay in those patients with serum albumin <3.5 gm% and BMI>25 kg/m2 and wound infection was found to be the most common complication among these patients. Conclusions: Majority of patients had serum albumin >3.5 gm/dl and more complications were seen with serum albumin <3.5 gm/dl which was statistically significant (p=0.01). Serum albumin is a good prognostic indicator because of its ability to detect protein energy malnutrition.